The value of academics: Evidence from academic independent director resignations in China - Chen, Jun; Garel, Alexandre; Tourani-Rad, Alireza (Journal of Corporate Finance, 2019)
In this paper, we use academic independent director resignations induced by the introduction of the Regulation 11 prohibiting academics from holding positions in Chinese public companies to examine their contribution to firm value. We document a negative market reaction to the issuance of the Regulation 11 and to the academic director resignations. The negative market reaction to academic director resignations is sizeable and hold when we further control for the influence of director, board, and firm characteristics. We next use heterogeneity in the market response to academic director resignations to study what the market values in academic directors. We find supportive evidence of a monitoring contribution and mixed evidence of advising and networking contributions. Finally, we show that in the two years following the issuance of the Regulation 11, companies with at least one academic director on their board prior to Regulation 11 underperform relative to companies without any academic directors. Overall, our results are consistent with a positive contribution of academic independent directors to firm value.